A Comparative Analysis and Development of Legislative Regulatory Framework of Naturopathy and Traditional Medicines Practices in Southern Africa Region - (:unkn) unknown (My University, 2024)
Objectives: Law and policy are critical instruments for enhancing health systems. The development of modern medicine relies heavily on stringent laws and policies. Additionally, the legislative framework for naturopathy and traditional complementary alternative medicines emphasizes the registration of both products and practitioners. This paper aims to examine the legislative regulatory framework governing naturopathic practices and other traditional complementary medicines in the Southern African region. Methods: This study involves a comprehensive review of various health laws and policy documents across Southern African countries. A country-specific analysis is conducted using keywords such as "naturopathic law," "naturopathic medicine practice," "legislation," "traditional medicine act," "alternative medicine act," and "healthcare laws." Results: The findings indicate that Southern African nations have well-established laws pertaining to naturopathy, as well as distinct regulations for traditional medicine. These countries recognize naturopathy and other complementary therapies as part of allied health professions. Moreover, there is a minimum educational requirement for registration as a traditional medicine healer, which applies to alternative complementary medicines. Conclusions: The research reveals that specific laws regulating naturopathic practice exist in Southern African countries. This commentary on the legislative regulatory framework for naturopathic and other traditional complementary medicines aims to inform public health decisions in Africa.
Keywords: African Research